Long‐term outcome of transendoscopic oesophageal mass ablation in dogs with Spirocerca lupi ‐associated oesophageal sarcoma. (10th October 2015) - Shipov, A.; Kelmer, G.; Lavy, E.; Milgram, J.; Aroch, I.; Segev, G.
Abstract : Oesophageal sarcoma is a potential sequel of Spirocerca lupi infection. Oesophageal mass excision can be performed by open chest surgery. The objectives of this observational study were to evaluate the feasibility, short‐term morbidity and long‐term outcome of transendoscopic oesophageal mass ablation in dogs with spirocercosis‐associated oesophageal neoplasia. A 9 mm video‐endoscope and laser or electrocauterisation were used to debulk the oesophageal mass. Long‐term follow‐up was done by telephonic interviews. Fifteen dogs were included. The median tumour size was 5 cm (range 3.5–9). The median procedure time was 75 minutes (range 35–165) and was deemed successful in 12/15 dogs (80 per cent). Recovery was uneventful in all dogs. Immediate complications included oesophageal damage (two dogs) oesophageal perforation (one dog) and a focal thermal damage (one dog). The median hospitalisation time of all dogs was less than one day, with all but two discharged on the procedure day. The median survival time, available in nine dogs that were followed, was 202 days (range 51–691). Four of these dogs (44 per cent) survived more than six months, of which three survived more than one year. In conclusion, transendoscopic oesophageal mass ablation might be considered an alternative, palliative procedure for open‐chest oesophageal surgery. It has comparable long‐term survival, lower morbidity, short hospitalisation time and relatively low cost.